การใช้รีโมทเซนซิงเพื่อตรวจสอบการเปลี่ยนแปลงในบริเวณชายฝั่งบ้านแหลมสิงห์ จังหวัดสมุทรปราการ - อจิรา เที่ยงตรง (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
This thesis is the study of the causes and rate of coastline change at Ban Laemsing, Samut Prakan Province by remote sensing techniques. the satellite images before and after Typhoons were analyzed to study the short term impact of the storms on coastline change. The results showed that Typhoon Gay caused shore deposition for 45,165.60 square meters and Typhoon Linda caused shore erosion for 120,261.38 square meters. These selected satellite images were compared according to seasonal monsoons. The whole coast line were eroded between 1990 and 1999 at the rates between 0.42 and 0.38 meters per month. Data between 1994 and 1997 indicated that the depositional rates were between 0.94 and 0.09 meters per month. By using color density slicing method to investigate the suspended sediment concentration in year 1989, 1990, 1994 and 1997, it appeared that the suspended sediment varied seasonally according to monsoon wind driven currents. By dividing Ban Laemsing into two areas to study the long term of coastaline changes owing to the landuse change. The upper area had been eroded at 0.58 and 1.51 meters per year during 1974 to 1981 and 1981 to 1999 respectively, from aerial photographs and satellite images. However the lower area had been severely receded during both the first the and second periods on the average of 17.51 and 14.02 meters per year respectively.